Isotopic evidence revealing spatial heterogeneity for source and composition of sedimentary organic matters in Taihu Lake, China. (February 2020) - Li, Zhichun; Li, Xiang; Wang, Xuan; Ma, Jie; Xu, Jie; Xu, Xiaoguang; Han, Ruiming; Zhou, Yiwen; Yan, Xingcheng; Wang, Guoxiang
Graphical abstract: Highlights: δ 13 C and δ 15 N signal ranges of potential SOM sources were different in Taihu Lake. SOM sources presented obvious spatial heterogeneity across Taihu Lake. Isotopic model of Monte Carlo simulations well calculated SOM source proportion. Hydrodynamic force caused the gradient distribution of SOM source contributions. Abstract: Tracing the formation processes of sedimentary organic matter (SOM) pools is crucial for understanding the carbon cycling of lake ecosystems, yet the source and composition of SOM, especially their spatial heterogeneity, in large and shallow lakes are still far from clear. In this study, SOM and its potential organic matter (OM) sources, including terrestrial particulate organic matter (POM), algae and aquatic macrophytes, were systematically investigated in Taihu Lake. We highlight the application of the end-member mixing model (EMM) based on Monte Carlo simulations of δ 13 C and δ 15 N ratios to more precisely depict the spatial heterogeneity for source and composition of SOM in such a large and shallow lake. The isotopically distinct signatures of SOM well displayed its sources obviously corresponded to the observed ecotypes of algae-type lakeshores, macrophyte-type lakeshore and groove in reed-belt. The results of EMM presented the higher proportion of terrestrial POM (46.8%–55.0%) than algae source (13.8%–23.4%) and macrophytes sources (20.0%–30.0%) in sediments from estuary and open water regions. The relative contribution proportions from three potential OM sources statistically correlated with relative contents of clay, silt and sand in sediments. The hydrodynamic force affected the grain size of sediments and drove the gradient distribution of SOM source contributions. These isotopic evidences revealed that aquatic macrophytes, algae bloom, inflow/outflow rivers and hydrodynamic changes could cause the spatial heterogeneity of SOM source and composition in large and shallow eutrophic lakes.